Studi Tingkat Kerusakan Ruas Jalan Poros Pinrang Kecamatan Tiroang dengan Metode Pavement Condition Index (PCI) - Imam Fadly; Muh Takdir K (Jurnal Rekayasa Teknik, 2022)
Roads are important infrastructure in transportation that can affect the progress of the economic, social, cultural and political fields in a region. However, in some cases the planned age of the road is not in accordance with what is happening in the field. Often the condition of the road is already damaged before the service period expires. Severe road damage is not uncommon, especially in the Pinrang axle road area, Tiroang District. The purpose of this study was to determine the types of damage found on the surface layer of the Pinrang axle road, Tiroang District and to find out more effective handling methods, as well as determine the effectiveness of assessing road damage using the Pavement Condition Index (PCI) method. From the results of data processing we get the Pavement Condition Index (PCI) value for the Pinrang axis road, Tiroang sub-district is 37.63. From the Povement Condition Index (PCI) value obtained, the road segment is classified as poor (Poor) and based on the results of the pavement condition classification, this road section is included in the routine maintenance program as a proposed handling. Of all the types of damage that occurred, we know that the biggest damage is the damage to holes (potholes) with an area of 1283.33 m2 (51%). The possible cause of this damage is caused by repeated traffic loads, this happens because vehicles (trucks) that carry material products that cross the road are often overloaded.